Clinical significance of preoperative carcinoembryonic antigen level in patients with clinical stage IA non-small cell lung cancer - Maeda, Ryo; Suda, Takashi; Hachimaru, Ayumi; Tochii, Daisuke; Tochii, Sachiko; Takagi, Yasushi (Journal of Thoracic Disease, 2017)
Background: The objective of this study was to assess the preoperative serum carcinoembryonic antigen (CEA) level in patients with clinical stage IA non-small cell lung cancer (NSCLC) and to evaluate its clinical significance. Methods: Between January 2005 and December 2014, a total of 378 patients with clinical stage IA NSCLC underwent complete resection with systematic node dissection. The survival rate was estimated starting from the date of surgery to the date of either death or the last follow-up by the Kaplan-Meier method. Univariate analyses by log-rank tests were used to determine prognostic factors. Cox proportional hazards ratios were used to identify independent predictors of poor prognosis. Clinicopathological predictors of lymph node metastases were evaluated by logistic regression analyses. Results: The 5-year survival rate of patients with an elevated preoperative serum CEA level was significantly lower than that of patients with a normal CEA level (75.5% vs. 87.7%; P=0.02). However, multivariate analysis did not show the preoperative serum CEA level to be an independent predictor of poor prognosis. Postoperative pathological factors, including lymphatic permeation, visceral pleural invasion, and lymph node metastases, tended to be positive in patients with an elevated preoperative serum CEA level. In addition, the CEA level was a statistically significant independent clinical predictor of lymph node metastases. Conclusions: The preoperative serum CEA level was not an independent predictor of poor prognosis in patients with pathological stage IA NSCLC but was an important clinical predictor of tumor invasiveness and lymph node metastases in patients with clinical stage IA NSCLC. Therefore, measurement of the preoperative serum CEA level should be considered even for patients with early-stage NSCLC.